2013
DOI: 10.1016/j.jbi.2013.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Defining and measuring completeness of electronic health records for secondary use

Abstract: We demonstrate the importance of explicit definitions of electronic health record (EHR) data completeness and how different conceptualizations of completeness may impact findings from EHR-derived datasets. This study has important repercussions for researchers and clinicians engaged in the secondary use of EHR data. We describe four prototypical definitions of EHR completeness: documentation, breadth, density, and predictive completeness. Each definition dictates a different approach to the measurement of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
215
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 298 publications
(222 citation statements)
references
References 33 publications
5
215
0
2
Order By: Relevance
“…Improving accuracy of data in the health record: Medical records can be inaccurate, incomplete, and biased. [65] With increased patient demand for access to medical records [8] and increased incentives to provide that access in recent federal legislation [7], more patients may review their medical records and help correct mistakes they discover [66]. Furthermore, this practice may motivate clinicians to improve data collection and documentation.…”
Section: Benefitsmentioning
confidence: 99%
“…Improving accuracy of data in the health record: Medical records can be inaccurate, incomplete, and biased. [65] With increased patient demand for access to medical records [8] and increased incentives to provide that access in recent federal legislation [7], more patients may review their medical records and help correct mistakes they discover [66]. Furthermore, this practice may motivate clinicians to improve data collection and documentation.…”
Section: Benefitsmentioning
confidence: 99%
“…[10][11][12][13][14] This is a well-recognized problem; numerous efforts have been made to establish techniques to validate this data source. 12,[15][16][17][18][19][20] In a review of 35 empirical studies, Chan, Fowles, and Weiner found a substantial lack of agreement regarding which data quality (DQ) dimensions were important to assess. 12 The authors discovered that, of the included studies, "66 percent assessed accuracy, 57 percent completeness, and 23 percent data comparability."…”
Section: Introductionmentioning
confidence: 99%
“…Quality Knowledge Repository (QKR): We extracted DQC, their definitions and applicable measures, their relationships, and the computability of DQC in existing DQF (e.g. Kahn 15 , Weiskopf 18 from literature. We identified primitives existing in different DQF to develop a DQ metamodel and implemented it as the QKR.…”
Section: A Service Oriented Architecture For Assessing Quality Of Hetmentioning
confidence: 99%